THE IMPLEMENTATION OF DEMONSTRATION TECHNIQUE TO TEACH SPEAKING IN PROCEDURE TEXT OF THE X GRADERS OF SMAN 1 MAGETAN IN THE ACADEMIC YEAR 2013/2014 - Sulastri, Siti (English Teaching Journal, 2015)
Learning to speak is not easy especially for the learners. The teacher always finds that the students or the learners are often reluctant because they are shy and difficult to express themselves in front ofÂ other people, especially when they are being asked to give personal information or opinions. Besides they are rarely given a chance to practice their speaking. Because of less in practicing to speak English or even never, students are finally afraid of speaking. They are afraid of making mistakes, especially in grammar and pronounciation. To make the students have motivation in speaking, the teacher should be able to facilitate and encourage the students in order to speak English as much as possible. Therefore the teacher needs to create an atmosphere where the students will feel free to use language they learning, so the learners will not get bored in learning English.Â There were three steps in the implementation of demonstration technique, pre activity, while activity and post activity. In pre activity, the teacher always opened the lesson through greeting, asking the studentâ condition and checking the attendance list. The teacher also prepared the materials every meeting. Then the started to introduce the material and explained the demonstration technique. In whilst activity, the teacher always asked the students to bring things that they would present in the following day. Then the teacher asked the students to discuss the steps with their friends how to make something before they started to demonstrate their properties. After discussing, the students began to demonstrate their properties while practicing it directly in front of the class. After demonstrating, other students began to respond their friendâs presentation. In post activity, the teacher observed the students activity and controlled their interaction during teaching learning process. She always gave reward to the best performance students, and corrected the students mistakes.After the students had the implementation of demonstration technique, their speaking ability showed that 75 % scores were increasing. So demonstration technique gave positive effect to the studentsâ speaking ability. And it can be said that demonstration technique was interesting for the students in learningÂ speaking.The studentâ response toward the implementation of demonstration technique in the process of teaching speaking were good. It can be showed that most of them stated that the use of this technique were really interesting and made the students more active in class. They also agreed that it could help them practice speaking English bravely. It was because the teacher chose appropriate topics selected which was related to the studentsâ interest and daily lives.